KANDUNGAN BESI AIR SUMUR DI PERUMAHAN HUMA AKASIA JATIWARNA - PONDOK MELATI, BEKASI - Bagya Mujianto; Angki Purwanti; Siti Rismini (Jurnal Ilmu dan Teknologi Kesehatan, 2015)
Water with high concentration of iron (Fe) or mangan (Mn) is not clean, easily change itscolor into brownish, and smelly. Household water for drinking, bathing, and washing shouldmeet requirement mentioned in the Regulation of Ministry of Health number 416Menkes/Per/IX/1990 and 492Menkes/Per/IV/2010. It is said that maximum iron concentrationpermitted for clean water is 1 mg/l (Kepmenkes), while for drinking water is 0,3 mg/l .Thisresearch aims to analyze the iron concentration of the wells water fromHuma AkasiaHousing Complex, Jatiwarna Pondok Melati, Bekasi. The sample was dry season waterfrom 119 wells in4 blocks area. The iron wasanalyzed through atomic absorptionspectrophotometric (AAS), followed by correlation test. The research found that the averageof iron concentration was 0.217 mg/l, with minimum was 0.10 mg/l, and maximum was 3.68mg/l. There are 16 wells (13.4 %) contain iron concentration that do not meet governmentrequirement for clean water. The correlation test between iron concentration and the wellsdepth found P value was 0.018 with correlation value was 0.228. Therefore, for alpha 0.05can be concluded that deeper wells produce a higher iron concentration in its water. Highiron concentration is resulted from the well with more than 30 metres in depth.